Direct Catalytic Asymmetric Mannich-Type Reaction of an α-CF3 Amide to Isatin Imines - Yu, Jin-Sheng; Noda, Hidetoshi; Kumagai, Naoya; Shibasaki, Masakatsu (Synlett, 2019)
An α-CF3 amide underwent direct asymmetric Mannich-type reaction to isatin imines in the presence of a chiral catalyst comprising a soft Lewis acid Cu(I), a chiral bisphosphine ligand, and Barton’s base. The Mannich adduct was converted in one step into a unique tricycle bearing a trifluoromethylated chiral center and an α-tertiary amine moiety.
Keywords: asymmetric catalysis; copper catalysis; fluorine; Mannich reaction; heterocycle